Analisis Efektivitas Implementasi Program Lapak Baca Oleh Karang Taruna Dalam Meningkatkan Minat Baca Anak Di Wilayah Kelurahan Cakung Barat - Muhammad Ilham Aji Faturahman; Vingqi Andryany (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2022)
The purpose of this study was determine and analyze: 1) the effectiveness of the implementation of the reading stall program in increasing children’s interest in reading in the Cakung Barat sub-district, 2) the obstacles encountered in the effectiveness of the reading stall program implementation, and 3) the efforts given in overcoming the obstacles faced in the implementation of the reading stall program. This research use descriptive qualitative method. The subjects of this research were the organizers, managers, and residents of the Cakung Barat sub-district. Data was collected through observation, interviews, and documentation. Data analysis techniques used included data display, data reduction, and conclusion drawing. The results of the study show that 1) the implementation of the reading stall program has been running well and effectively, which can be seen from the enthuasism of visitors who come to borrow books or take partin monthly activities in order to increase children’s reading interest in the Cakung Barat sub-district; 2) the sense of responsibility among visitors who borrow books is still low, so that the number of books available decreases; and 3) this program provides education about a sense of responsibility to children as well as punishments such as cleaning the reading stall area for those who are late in returning books and fines for those who lose books